Pengajaran Bahasa Dalam Perspektif Sosiolinguistik - Moh. Muklis (UIN Sultan Aji Muhammad Idris Samarinda, 2011)
Teaching the language is not just transferred the knowledge from educators to students. Moreover, teaching the language must be transformed from an instructor to participant learning. Therefore a teacher must also understand the basic character and culture held by the learner. This broad knowledge must be prepared by those who teach students the language to the participants. Not just a question of mere knowledge, but understanding a teacher should include in-depth aspects in order to obtain optimal results. Learner's culture, the status of languages taught, academic ability, and other capabilities should be owned first by the teacher. Meanwhile mandatory capabilities such as understanding of the methods, strategies and approaches to learning and evaluation will be able to assist a teacher in order to succeed language learning purposes.